1993
DOI: 10.1111/j.1432-1033.1993.tb18058.x
|View full text |Cite
|
Sign up to set email alerts
|

Docking the mitochondrial inhibitor protein IF1 to a membrane receptor different from the F1‐ATPase β subunit

Abstract: Monoclonal antibodies reacting with the inhibitor protein (IF1) of the mitochondrial ATPase/ATP synthase complex did not modify the IF1‐induced inhibition of soluble F1 ATPase activity. On the contrary, they increased the ATPase activity of inverted electron‐transport particles without inducing a significant release of IF1 from these particles. This suggested that IF1 could be linked to a membrane protein when it was not inhibiting the ATPase activity. IF1 antibodies have been used to show that IF1 can bind no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
22
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 52 publications
1
22
0
Order By: Relevance
“…Nevertheless, the effects of the mutation must necessarily be subtle, 3 N. Hance and I. J. Holt, unpublished data. (37), yet this complex is considerably larger than 100 kDa and therefore likely involves at least one other protein, perhaps the 21-kDa protein partly characterized previously (38) . FIG.…”
Section: Discussionmentioning
confidence: 88%
“…Nevertheless, the effects of the mutation must necessarily be subtle, 3 N. Hance and I. J. Holt, unpublished data. (37), yet this complex is considerably larger than 100 kDa and therefore likely involves at least one other protein, perhaps the 21-kDa protein partly characterized previously (38) . FIG.…”
Section: Discussionmentioning
confidence: 88%
“…Such a proteolytic alteration could be accomplished by one of the death proteases or by another protease released through the action of a death protease. As to inhibitors, a precedent exists in the form of IF1, a small mitochondrial polypeptide that inhibits the ATPase activity of Complex V when the potential across the inner mitochondrial membrane is low (27)(28)(29)(30)(31)(32)(33)(34). This regulatory polypeptide prevents the destruction of ATP that would otherwise occur if for some reason the mitochondrial transmem- brane potential should transiently collapse (28).…”
Section: Discussionmentioning
confidence: 99%
“…First, it has been reported that besides binding the ␤ subunit of F 1 , IF 1 can bind another protein of low M r of the inner mitochondrial membrane (47) and this might lead to ⌬ m enhancement in respiring mitochondria. This hypothesis does not seem acceptable because native PAGE analysis in our hand never showed the inhibitor protein in bands other than the IF 1 -ATP synthase complexes (Fig.…”
Section: Discussionmentioning
confidence: 99%